The Influence of Work-Life Balance and Burnout on the Performance of Relationship Credit Employees at PT. Bank Rakyat Indonesia Tbk, Medan - Nirwani, Sekar; Sienny, Sienny (Holistic Science, 2025)
This study aims to analyze the influence of Work Life Balance and Burnout on Employee Performance at PT. Bank Rakyat Indonesia Tbk, Medan. Work Life Balance is the interaction between work and other activities that include family, community, leisure time, and personal development, while Burnout can be interpreted as a syndrome due to chronic stress in the workplace that can be characterized by feelings of exhaustion or fatigue, increased mental distance from one's work or feelings of negativism related to one's work. The research method uses a descriptive quantitative approach. The population in this study were all Relationship Credit employees of PT. Bank Rakyat Indonesia Tbk, Medan and the number of samples used saturated samples, namely 71 respondents. Data analysis used multiple linear regression analysis. Research data were collected using a questionnaire. With a Cronbach Alpha reliability of Work Life Balance of 0.856, Burnout of 0.739, and employee performance of 0.873. The results of the study indicate that: (1) There is a positive and significant influence between Work Life Balance on Employee Performance; (2) There is a positive and significant influence between Burnout on Employee Performance; (3) There is a positive and significant influence between Work Life Balance and Burnout together on Employee Performance.